Characterization of the enzymes involved in the methylerythritol phosphate pathway with a view to development of broad-spectrum antibiotics including anti-tuberculosis drugs - Eoh, Hyung-Jin, author; Brennan, Patrick, advisor; Crick, Dean, advisor (Colorado State University. Libraries, 2007)
Isopentenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP) are precursors of all isoprenoids, many of which play an essential role for the survival of organisms. To date, two separate pathways have been revealed for their biosynthesis. The mevalonate (MVA) pathway is utilized by eukaryotes, algae, archaca-bacteria and some Gram-positive bacteria. Besides the MVA pathway, an alternative route (the rnethylerythritol phosphate pathway; MEP pathway) has been discovered relatively recently. The MEP pathway is utilized exclusively by Gram-negative bacteria, plants and some Gram-positive bacteria. The enzymes in the MEP pathway are considered as potential targets for novel broad-spectrum antibacterial drugs, since they are absent in humans and the disruption of any genes encoding the enzymes in this pathway in E. coli showed lethal phenotypes. The severity of bioterrorist threats has been increased by the emergence of antibiotic-resistant bacilli. An ideal state of preparedness for pending bioterrorist attacks would be achieved by continuous development of novel antibiotics. The Centers for Disease Control and Prevention (CDC) and the National Institute of Allergy and Infectious Diseases (NIAID) have categorized lists of biological diseases/agents based on their potential lethality. Most of the organisms utilize the MEP pathway. Thus, the enzymes in the MEP pathway can provide potential drug targets to overcome drug resistant bacilli. In order to improve the quality of bioterrorism preparedness and tuberculosis control, we have identified and characterized the enzymes in the MEP pathway of the human pathogens; Salmonella typhi, Vibrio cholerae, Burkholderia mallei, and M. tuberculosis. In addition, we developed in vitro high throughput screening (HTS) assays to find specific inhibitors. In the present dissertation, 4-(cytidinc 5'-diphosphate)-2-C-methyl-D-erythritol synthase and 4-(cytidine 5'-diphosphate)-2-C-methyl-D-erythritol kinase were cloned, overexpressed, and purified for the purpose of characterizing the enzymes and developing in vitro HTS assays. In addition, in vitro enzyme assay of M. tuberculosis 1-deoxy-D-xylulose 5-phosphate synthase was optimized and applied to screen specific inhibitors. In vitro HTS assays used in this study are facile, direct, and relatively inexpensive compared to NMR spectroscopy or the HPLC based assays, previously employed for characterizing the orthologs of other organisms. We expect inhibitors screened through the in vitro HTS assays to show broad-spectrum activity. We anticipate the enzymes the MEP pathway studied in this dissertation are potential targets for developing novel broad-spectrum antibiotics and it would open up an entirely new class of antibiotics.
Keywords: antibiotics; antituberculosis drugs; bacterial pathogens; bioterrorism; methylerythritol phosphate; Mycobacterium tuberculosis; microbiology